Functional and genetic predisposition to rhinovirus lower respiratory tract infections in prematurely born infants - Drysdale, S; Alcazar, M; Wilson, T; Smith, M; Zuckerman, M; Hodemaekers, H; Janssen, R; Bont, L; Johnson, S; Greenough, A (Springer, 2016)
Term born infants are predisposed to human rhinovirus (HRV) lower respiratory tract infections (LRTI) by reduced neonatal lung function and genetic susceptibility. Our aim was to investigate whether prematurely born infants were similarly predisposed to HRV LRTIs. Infants born less than 36 weeks of gestational age were recruited. Prior to neonatal/maternity unit discharge, lung function (functional residual capacity by helium gas dilution and multiple breath washout, lung clearance index and compliance (Crs) and resistance (Rrs) of the respiratory system) was assessed and DNA samples assessed for eight single nucleotide polymorphisms (SNPs) in seven genes: ADAM33, IL10, MMP16 NFκB1A, SFTPC, VDR and NOS2A. Infants were prospectively followed until one year corrected age. Nasopharyngeal aspirates (NPAs) were sent whenever an infant developed a LRTI and tested for 13 viruses. One hundred and six infants were included in the analysis. Infants who developed HRV LRTIs had reduced Crs (1.6 versus 1.2 mL/cmH2O/kg, p=0.044) at 36 weeks postmenstrual age. A SNP in the gene coding for the vitamin D receptor was associated with the development of HRV LRTIs (p=0.047) and other respiratory viral infections (p=0.02). Conclusion:Prematurely born infants may have both a functional and genetic predisposition to HRV LRTIs.